The Beijing Climate Center atmospheric general circulation model: description and its performance for the present-day climate - Wu, Tongwen; Yu, Rucong; Zhang, Fang; Wang, Zaizhi; Dong, Min; Wang, Lanning; Jin, Xia; Chen, Deliang; Li, Laurent (Climate Dynamics, 2010)
International audience The Beijing Climate Center atmospheric general circulation model version 2.0.1 (BCC_AGCM2.0.1) is described and its performance in simulating the present-day climate is assessed. BCC_AGCM2.0.1 originates from the community atmospheric model version 3 (CAM3) developed by the National Center for Atmospheric Research (NCAR). The dynamics in BCC_AGCM2.0.1 is, however, substantially different from the Eulerian spectral formulation of the dynamical equations in CAM3, and several new physical parameterizations have replaced the corresponding original ones. The major modification of the model physics in BCC_AGCM2.0.1 includes a new convection scheme, a dry adiabatic adjustment scheme in which potential temperature is conserved, a modified scheme to calculate the sensible heat and moisture fluxes over the open ocean which takes into account the effect of ocean waves on the latent and sensible heat fluxes, and an empirical equation to compute the snow cover fraction. Specially, the new convection scheme in BCC_AGCM2.0.1, which is generated from the Zhang and McFarlane’s scheme but modified, is tested to have significant improvement in tropical maximum but also the subtropical minimum precipitation, and the modified scheme for turbulent fluxes are validated using EPIC2001 in situ observations and show a large improvement than its original scheme in CAM3. BCC_AGCM2.0.1 is forced by observed monthly varying sea surface temperatures and sea ice concentrations during 1949-2000. The model climatology is compiled for the period 1971-2000 and compared with the ERA-40 reanalysis products. The model performance is evaluated in terms of energy budgets, precipitation, sea level pressure, air temperature, geopotential height, and atmospheric circulation, as well as their seasonal variations. Results show that BCC_AGCM2.0.1 reproduces fairly well the present-day climate. The combined effect of the new dynamical core and the updated physical parameterizations in BCC_AGCM2.0.1 leads to an overall improvement, ...